The impact of greenspace and condition of the neighbourhood on child overweight. (21st March 2017) - Schalkwijk, Annemarie A H; van der Zwaard, Babette C; Nijpels, Giel; Elders, Petra J M; Platt, Lucinda
Abstract: Background: Childhood overweight/obesity has been associated with environmental, parenting and socioeconomic status (SES) factors. This paper assesses the influence of the amount of green space, accessibility to a garden and neighbourhood condition on being overweight/obese. It investigates whether parental behaviours moderate or mediate this influence and evaluates the interaction of SES with environmental context. Methods: 6467 children from the UK Millennium Cohort Study living in England were analysed. We estimated logistic regressions to examine the initial association between environment and overweight. Subsequently, parenting determinants comprising: food consumption, physical activity, rules and regularity were evaluated as moderators or mediators. Lastly SES related variables were tested as moderators or mediators of the associations. Results: Statistically significant associations were found between low levels of green space, no access to a garden, run down area and childhood overweight/obesity [odds ratio (OR) [95% confidence interval (CI)] respectively: 1.14 (1.02–1.27), 1.35 (1.16–1.58), 1.22 (1.05–1.42)]. None of the parental constructs mediated or moderated the relationships between environment and childhood overweight/obesity. Including SES, parental education moderated the effect of environmental context. Specifically, among lower educated households lack of garden access and less green space was associated with overweight/obesity; and among higher educated households poor neighbourhood condition influenced the probability of overweight/obesity respectively: 1.38 (1.12–1.70) OR 1.38, 95% CI (1.21–1.70). Conclusions: This study suggests that limits on access to outdoor space are associated with future childhood overweight/obesity although the ways in which this occurs are moderated by parental education level.